Model Pemberdayaan Berbasis Masjid: Pengolahan Air Wudhu dan Penguatan Kelembagaan Mengatasi Krisis Air Jakarta Utara - Rafiuddin Syam; Rizky Priambodo; Heri Firmansyah; Kiyotaka Izumi (Bahasa Indonesia, 2026)
The clean water crisis in North Jakarta, particularly in the Sunter Jaya area, is worsening due to domestic and industrial waste pollution combined with limited water treatment infrastructure. This article reports a technology-based community service program that converts the ablution (wudhu) water source at Al-Mukhlish Mosque into a supply of ready-to-drink water. An integrated approach combining sedimentation, activated carbon-zeolite adsorption, Reverse Osmosis (RO), and UV-C sterilization was applied to address three problems: limited access to clean water, low community awareness of water recycling, and minimal treatment infrastructure. Implementation followed four stages: (1) socialization through focus group discussions with the mosque board (DKM) and residents; (2) phased technical training; (3) installation of an FRP filter unit at the mosque; and (4) evaluation through water-quality testing and a resident satisfaction survey. The program reduced Total Dissolved Solids (TDS) from 500 mg/L to 50 mg/L, eliminated 99% of pathogenic bacteria including E. coli, and raised the operating skills of 80% of training participants. A water-management group was formed, and affordable monthly maintenance costs (IDR 500,000) support the program's sustainability. The model advances SDG 6 (Clean Water and Sanitation) and offers a replicable, mosque-based approach to the urban clean-water crisis that combines technology, education, and community participation.